The enterovirus 71 A-particle forms a gateway to allow genome release: a cryoEM study of picornavirus uncoating. - Kristin L Shingler (PLoS Pathogens, 2013)
Since its discovery in 1969, enterovirus 71 (EV71) has emerged as a serious worldwide health threat. This human pathogen of the picornavirus family causes hand, foot, and mouth disease, and also has the capacity to invade the central nervous system to cause severe disease and death. Upon binding to a host receptor on the cell surface, the virus begins a two-step uncoating process, first forming an expanded, altered "A-particle", which is primed for genome release. In a second step after endocytosis, an unknown trigger leads to RNA expulsion, generating an intact, empty capsid. Cryo-electron microscopy reconstructions of these two capsid states provide insight into the mechanics of genome release. The EV71 A-particle capsid interacts with the genome near the icosahedral two-fold axis of symmetry, which opens to the external environment via a channel ∼10 Å in diameter that is lined with patches of negatively charged residues. After the EV71 genome has been released, the two-fold channel shrinks, though the overall capsid dimensions are conserved. These structural characteristics identify the two-fold channel as the site where a gateway forms and regulates the process of genome release.